Why does ticagrelor induce dyspnea? - Cattaneo, Marco; Faioni, Elena M. (Thrombosis and Haemostasis, 2012)
In studies that compared the reversible P2Y12 inhibitor ticagrelor with the irreversible inhibitor clopidogrel, dyspnea was observed more frequently among ticagrelor-treated patients than among clopidogreltreated patients. Because dyspnea was not associated with acidosis, pulmonary or cardiac dysfunction, alterations in the mechanisms and pathways of the sensation of dyspnea may be involved in its pathogenesis. It has been hypothesised that the sensation of dyspnea in ticagrelor-treated patients is triggered by adenosine, because ticagrelor inhibits its clearance, thereby increasing its concentration in the circulation. However, dipyridamole, a much stronger inhibitor of adenosine clearance than ticagrelor, usually does not cause dyspnea. We hypothesise that inhibition of P2Y12 on sensory neurons increases the sensation of dyspnea, particularly when reversible inhibitors are used. We base our hypothesis on the following considerations: 1) cangrelor and elinogrel, which, like ticagrelor, are reversible P2Y12 inhibitors, also increase the incidence of dyspnea;2) it is biologically plausible that inhibition of P2Y12 on sensory neurons increases the sensation of dyspnea;3) inhibition of P2Y12 on platelets (which do not have a nucleus) by clopidogrel is permanent, despite the once daily administration and the short plasma half-life of the inhibitor;4) in contrast, inhibition of P2Y12 on neurons by clopidogrel may be temporary and transient, because neurons have a nucleus and can therefore rapidly replace the inhibited receptors with newly synthetised ones;5) inhibition of P2Y12 on neurons by reversible inhibitors is permanent, because the plasma drug concentration is maintained high by repeated dosing, in order to ensure permanent inhibition of platelet P2Y12.
Keywords: ADP receptors; arterial thrombosis; nervous system